نظام المعلومات التسويقي في شركات التأمين ودوره في اتخاذ القرارات التسويقية (Journal of Accounting and Financial Studies ( JAFS ), 2020)
Seek Iraqi insurance companies to face the global changes today that may affect the overall performance of the company, it must find an effective means of providing everything you need company information, and by increasing attention to administrative operations in general, especially the marketing process, which from its core focus on activities related to elements of the marketing mix, as the success of any company in achieving the planned objectives, linked to its ability to make sound decisions in the context of the above elements, for the latter of great importance, especially if based on facts and indicators obtained from the reality of my knowledge accurate and that constitute the so-called (marketing information system).